Role of Dietary Amino Acids and Nutrient Sensing System in Pregnancy Associated Disorders - Tarique Hussain; Tarique Hussain; Tarique Hussain; Bie Tan; Ghulam Murtaza; Elsayed Metwally; Huansheng Yang; Muhammad Saleem Kalhoro; Dildar Hussain Kalhoro; Muhammad Ismail Chughtai; Yulong Yin (Frontiers Media S.A., 2020)
Defective implantation is related to pregnancy-associated disorders such as spontaneous miscarriage, intrauterine fetal growth restriction and others. Several factors proclaimed to be involved such as physiological, nutritional, environmental and managemental that leads to cause oxidative stress. Overloading of free radicals promotes oxidative stress, and the internal body system could not combat its ability to encounter the damaging effects and subsequently leading to pregnancy-related disorders. During pregnancy, essential amino acids display important role for optimum fetal growth and other necessary functions for continuing fruitful pregnancy. In this context, dietary amino acids have received much attention regarding the nutritional concerns during pregnancy. Arginine, glutamine, tryptophan and taurine play a crucial role in fetal growth, development and survival while ornithine and proline are important players for the regulation of gene expression, protein synthesis and angiogenesis. Moreover, amino acids also stimulate the mammalian target of rapamycin (mTOR) signaling pathway which plays a central role in the synthesis of proteins in placenta, uterus and fetus. This review article explores the significances of dietary amino acids in pregnancy development, regulation of nutrient-sensing pathways such as mTOR, peroxisome proliferator-activated receptors (PPARs), insulin/insulin-like growth factor signaling pathway (IIS) and 5' adenosine monophosphate-activated protein kinase (AMPK) which exhibit important role in reproduction and its related problems. In addition, the antioxidant function of dietary amino acids against oxidative stress triggering pregnancy disorders and their possible outcomes will also be enlightened. Dietary supplementation of amino acids during pregnancy could help mitigate reproductive disorders and thereby improving fertility in animals as well as humans.